(2x-1) (4x^2+2x+1) -2x (2x-1)…

Тема в разделе "Алгебра", создана пользователем Romka0647, 5 сен 2016.

  1. Romka0647

    Romka0647 Мелюзга

    Регистрация:
    26 мар 2013
    Сообщения:
    0
    Симпатии:
    0
    (2x-1) (4x^2+2x+1) -2x (2x-1) (2x+1)=
     
  2. Skarasev8

    Skarasev8 Мелюзга

    Регистрация:
    14 янв 2013
    Сообщения:
    0
    Симпатии:
    0
    (2x-1) (4x^2+2x+1) -2x (2x-1) (2x+1) (2x-1) (4x^2+2x+1)=8x^3+4x^2+2x-4x^2-2x-1=8x^3 -12x (2x-1) (2x+1)=2x (4x^2-1)=8x^3-2x (2x-1) (4x^2+2x+1) -2x (2x-1) (2x+1)=8x^3 -1 — (8x^3-2x)=2x-1 Ответ: 2 х-1
     

Поделиться этой страницей